Engineering for offshore fish farming proceedings of the conference organized by the Institution of Civil Engineers, and held in Glasgow on 17-18 October 1990. (Thomas Telford, 1990)
The search for cleaner waters and the need to avoid polluting coastlines, combined with a general desire for expansion, have meant that farmers are constructing farms in ever more aggressive wave environments. This work draws on the international experience of engineers and aquaculturalists in an attempt set up a design philosophy.